Deciphering the development of smart and sustainable tourism cities in Southeast Asia: A call for research - Stephenson, M. L. *; Dobson, G. (Society for South-East Asian Studies, 2020)
A recognized desire is noticeable within ASEAN nations to develop more sustainable approaches to urban development and tourism. One solution has been to promote the expansion of both smart cities and smart tourism practices. Recently, these smart approaches have been implemented across a variety of different cities and locales. The purpose of this paper is to discuss the potential for further research in developing relation- ships between ‘smart cities’ and ‘smart tourism’ practices in Southeast Asia. Rather than present a review of the entire region, three potential case studies located in Myanmar, Lao PDR, and Thailand are discussed. These include Yangon as a case of smart approaches in a primary city, Vientiane as a case of smart approaches in a smaller city, and Phuket as a case of smart approaches in an area which suffers from overtourism. The authors maintain that this type of case study research within ASEAN states can provide critical insights and local solutions to the advancement of smart and sustainable tourism destinations.